Functional Status After Pulmonary Rehabilitation as a Predictor of Weaning Success and Survival in Patients Requiring Prolonged Mechanical Ventilation - Keng, Li-Ta; Liang, Sheng-Kai; Tseng, Chi-Ping; Wen, Yueh-Feng; Tsou, Ping-Hsien; Chang, Chia-Hao; Chang, Lih-Yu; Yu, Kai-Lun; Lee, Meng-Rui; Ko, Jen-Chung (Frontiers in Medicine, 2021)
Background: Comprehensive rehabilitation programs are recommended for patients with prolonged mechanical ventilation (PMV) to facilitate functional recovery and ventilator weaning, but whether the functional status after rehabilitation influences outcome has not been clearly evaluated. This study aimed to investigate the association between post-rehabilitation functional status and weaning and survival outcome in PMV patients. Methods: We retrospectively enrolled PMV patients admitted to the respiratory care center (RCC), a post-ICU weaning facility with protocolized rehabilitation program, from January 2016 through December 2017. Functional status was measured by the de Morton Mobility Index (DEMMI), with a cut-off value set at 20 points. The primary outcomes were the weaning status at RCC discharge and hospital survival. The secondary outcomes were overall survival and survival at 3 months after RCC discharge. We followed patients until 3 months after RCC discharge or death. Logistic and Cox regressions were performed to identify significant parameters associated with weaning success and survival. Results: In total, 320 patients were enrolled. The weaning success rate was 71.6%. The survival rate at RCC discharge, hospital discharge and 3 months after RCC discharge was 89.1%, 77.5% and 66.6%, respectively. Post-rehabilitation DEMMI >= 20 (odds ratio [OR], 3.514; 95% confidence interval [CI], 1.436-8.598; P = 0.006) was the most significantly associated with weaning success. The weaning success and higher post-rehabilitation DEMMI were the two most significant independent factors associated with both hospital survival (weaning success, OR, 12.272; 95% CI, 5.281-28.517; P < 0.001; post-rehabilitation DEMMI >= 20, OR, 6.298; 95% CI, 1.302-30.477; P = 0.022) and survival at 3 months after RCC discharge (weaning success, OR, 38.788; 95% CI, 11.505-130.762; P < 0.001; post-rehabilitation DEMMI >= 20, OR, 4.830; 95% CI, 1.072-21.756; P = 0.040). Post-rehabilitation DEMMI >= 20 remained significantly association with overall survival at 3 months after RCC discharge (hazard ratio, 0.237; 95% CI, 0.072-0.785; P = 0.018). Conclusions: Post-rehabilitation functional status of PMV patients was independently associated with weaning success, as well as hospital and 3-month overall survival after RCC discharge. Post-rehabilitation, but not pre-rehabilitation, functional status was a significant parameter associated with weaning success and survival in patients requiring PMV.